Sistem Pelepasan Informasi Rekam Medis Dalam Menjamin Aspek Hukum Kerahasiaan Rekam Medis Di RSU. Imelda Pekerja Indonesia Tahun 2023 - Ritonga, Abdul Malik; Manurung, Sarida Surya; Nurani , Ramada; Manurung, Jonni Sastra (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
Privacy, confidentiality and release of information are communications containing certain confidential information provided by patients to their doctors to be kept confidential, unless the patient has given written consent to release the information from their medical records. The aim of this research is to determine the procedures for the medical record information release system in ensuring the legal aspects of confidentiality at RSU. Imelda Indonesian Worker. This type of research is descriptive, namely a research method carried out with the aim of creating an objective picture of a situation. Research time is from January to August 2023 at RSU. Imelda Indonesian Worker. The subjects in this research were medical records officers, the research informant was the head of medical records. From the results of the research, it is known that the procedures for the release of medical record information system run in accordance with SPO number 002/SPO/MRMIK/2022, there is no specific SPO regarding the confidentiality of medical records but confidentiality has been carried out well in accordance with the SPO for the release of medical record information and in line with the 24 year Health Ministerial Regulation. 2022 regarding medical records, at RSU. Imelda, an Indonesian worker, releases a lot of information for insurance. The obstacle in releasing medical information is patients/families who do not bring a power of attorney and identification, where the patient's family does not understand the importance of a power of attorney. It is hoped that hospitals will create special SOPs regarding the confidentiality of medical records and provide information to patients/families about the requirements and procedures for releasing medical information by placing banners or posters in the information section or other strategic places.